Rang and Dale's pharmacology - Rang, H.P; Dale, M. Maureen; Flower, R. J. (Rod J.), 1945-; Henderson, G. (Graeme) (Elsevier Churchill Livingstone, 2016)
For 25 years, Rang and Dale's Pharmacology has delivered the core basic and clinical science information required by students and healthcare practitioners worldwide. Authors H. P. Rang, J. M. Ritter, R. J. Flower, and G. Henderson have ensured that the 8th Edition of this easy-to-read, comprehensive text continues the tradition of excellence with new coverage of drugs affecting the skin and new components online at Student Consult.